A study on the factors that influence Ad avoidance and Ad competition of skippable in-stream Ads on YouTube videos - Gloria, Herylle Ivee G. (2023)
Many marketers or advertisers had shifted their efforts to digital advertising. Due to the fact that YouTube has one of the highest monthly user counts among social media platforms, marketers or advertisers have made use of the platform as a medium for advertising by running in-stream ads on YouTube videos. However, since ad avoidance presents a problem for marketers or advertisers, it is important to understand the factors that affect this behavior. That being said, this quantitative study was conducted to investigate the factors that affect Filipino YouTube users' attitudes when they see skippable in-stream ads on YouTube videos and their effect on ad avoidance and ad completion. The study looked at four variables, namely, entertainment, informativeness, credibility, and irritation. Data gathered from 101 respondents were analyzed through Pearson correlation coefficient and regression analysis, where it was found that all four factors analyzed ? entertainment, informativeness, credibility, and irritation?are correlated with consumers' attitudes towards skippable in-stream ads on YouTube videos; however, only entertainment, credibility, and irritation have a significant influence on the consumer?s attitude towards skippable in-stream ads on YouTube videos. The findings of the study indicate that a consumer's attitude towards skippable in-stream ads on YouTube videos was positively influenced by entertainment and credibility, whereas their attitudes were negatively influenced by irritation. Furthermore, the results also showed that ad avoidance is negatively influenced by consumers' attitudes towards skippable in-stream ads on YouTube videos. The findings also suggested that ad completion is not always implied by the absence of ad avoidance.